Effect of dam methylation on the activity of the E. coli replication origin, oriC. - Messer, W (1985)
Methylation of GATC sites by the dam methylase is required for efficient initiation of DNA replication at the replication origin, oriC, of Escherichia coli. This is demonstrated by the inability of minichromosomes to be maintained in dam mutant strains. The requirement for methylated GATC sites is less stringent in vitro than in vivo. The time required for complete methylation of the origin region apparently determines the minimal spacing of replication forks on the chromosome.